REDEFINISI PEREMPUAN CANTIK DALAM CERPEN RATIH KUMALA DAN AGUS NOOR - , LA ODE GUSMAN NASIRU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was started from the problem of two female characters of TPI and KYJ that are intimidated by the ideal beauty creation from outside themselves. The female characters were analyzed being person who cannot choose the way how to express who they truly are, because many authors have set a beautiful construction over their bodies. It is similar to what has been done by the beauty myth against women in real life. This principle was applied by the authors to their characters. Thus, this research attempts to examine how the beauty myth oppresses women in real life, and how the authors redefined the beauty myth to eventually oppress the characters in the short story. This research used theory of the myth of beauty which developed by Naomi Wolf. This theory was needed to help the researcher in seeing the problems of beauty which developed in short story by Kumala and Noor. The myth of beauty can be a magnifier in order to analyze the extent of this theory in oppressing women and how the author subdued and eventually followed to set the standards of the ideal beauty. In this research, it was found that through TPI and KYJ, both authors attempted to break away from the restraints of the beauty myth. However, they even unconsciously eternalize it through the establishment concept of ideal to the characters. Contestation occurred between the authorsâ desire to get out of the beauty myth and the fact that they are still locked in handfuls of the beauty myth itself. Ideas collisions occur not only between the authors and the beauty myth, but also between the characters and the authors. In order to face the reality that binds and oppress their bodies, the characters tried to break the ideal concept that has been redefined by the authors. The final result is the contestation and collisions further strengthen the fact that the concept of ideal beauty is merely relative.